Architecture and implementation principles of data exchange equipment for safety related systems - Malinovsky, M. L.; Karaman, D. G. (My University, 2016)
The problem of linking separate subsystems in complex information management systems created and supported by various independent companies is touched upon. The analysis of the key features and differences in safety assurance practices in a variety of management systems is carried out, as well as the possibility of their application in the design and development of linking devices is considered. Principles of construction data exchange equipment between systems having different communication protocols, architecture and safety assurance ideology, while ensuring compliance with the requirements for reliability and safety at the level of alignment are given.

У статті порушено проблему ув’язки окремих підсистем у складі комплексних інформаційно-керуючих систем, що створюються і підтримуються різними компаніями-розробниками. Виконано аналіз ключових особливостей і відмінностей методів забезпечення безпеки в різних системах управління, а також розглянута можливість їх застосування при проектуванні і розробці засобів ув’язки. Наведено принципи побудови апаратури сполучення систем, що мають різні протоколи обміну даними, архітектуру і ідеологію забезпечення безпеки, забезпечуючи при цьому виконання вимог до надійності і безпеки на рівні ув’язки.
Архітектура та принципи реалізації апаратури сполучення систем, що пов'язані з безпекою
Keywords: control systems; microprocessor centralization; linking devices; data exchange equipment; safety; системи управління; мікропроцесорна централізація; засоби ув'язки; апаратура сполучення